Sterilization of coconut milk in flexible packages via ohmic-assisted thermal sterilizer. (July 2021) - Tiravibulsin, Chavis; Lorjaroenphon, Yaowapa; Udompijitkul, Pathima; Kamonpatana, Pitiya
Abstract: Extreme heat treatments of canned coconut milk might reduce overall product quality. Therefore, an ohmic-assisted thermal sterilizer (OATS) may be able to preserve packaged coconut milk as an alternative to an overpressure retort. OATS involves converting electrical energy immediately into heat inside medium, which is then transferred to the food packages. This differs from conventional retorts which relied primarily on heat transfer. To ensure food safety, the OATS was microbiologically validated using Clostridium sporogenes spores. Physicochemical property and aroma compound profile differences in coconut milk sterilized at F0 of 5.2 min using OATS were compared with conventional water spray retort. OATS completely inactivated C. sporogenes spores with more than 5 log CFU/mL at 121.1 °C for 5 min. The total processing time for OATS was 27 min using 32% less energy compared to the 42 min for the retort, indicating the higher process efficiency of OATS. OATS food products surpassed conventional retort properties in appearance, with minor color changes; off-odor, having a lower cooked odor by reducing methyl-ketone and Maillard reaction products; and desired aromas, by preserving contributors such as ethyl octanoate and δ-lactones. Consequently, OATS could potentially produce sterile coconut milk with minimal changes in appearance while decreasing off-odor formation. Graphical abstract: Image 1 Highlights: Foods with high fat content could be sterilized using ohmic assisted-thermal sterilizer (OATS). OATS inactivated Clostridium sporogenes spores more than 5 log cfu/mL at 121.1 °C for 5 min. OATS minimized property changes, and preserved desired coconut milk aromas. Ohmic heating reduced total processing time and showed higher energy efficiency. OATS is recommended for sterilization of packaged foods.